Poly(ADP-ribose) polymerase-1 regulates fibroblast activation in systemic sclerosis - Zhang, Yun; Pötter, Sebastian; Chen, Chih-Wei; Liang, Ruifang; Gelse, Kolja; Ludolph, Ingo; Horch, Raymund E.; Distler, Oliver; Schett, Georg; Distler, Jörg; Dees, Clara (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: The enzyme poly(ADP-ribose) polymerase-1 (PARP-1) transfers negatively charged ADP-ribose units to target proteins. This modification can have pronounced regulatory effects on target proteins. Recent studies showed that PARP-1 can poly(ADP-ribosyl)ate (PARylate) Smad proteins. However, the role of PARP-1 in the pathogenesis of systemic sclerosis (SSc) has not been investigated. METHODS: The expression of PARP-1 was determined by quantitative PCR and immunohistochemistry. DNA methylation was analysed by methylated DNA immunoprecipitation assays. Transforming growth factor-β (TGFβ) signalling was assessed using reporter assays, chromatin immunoprecipitation assays and target gene analysis. The effect of PARP-1 inactivation was investigated in bleomycin-induced and topoisomerase-induced fibrosis as well as in tight-skin-1 (Tsk-1) mice. RESULTS: The expression of PARP-1 was decreased in patients with SSc, particularly in fibroblasts. The promoter of PARP-1 was hypermethylated in SSc fibroblasts and in TGFβ-stimulated normal fibroblasts. Inhibition of DNA methyltransferases (DNMTs) reduced the promoter methylation and reactivated the expression of PARP-1. Inactivation of PARP-1 promoted accumulation of phosphorylated Smad3, enhanced Smad-dependent transcription and upregulated the expression of TGFβ/Smad target genes. Inhibition of PARP-1 enhanced the effect of TGFβ on collagen release and myofibroblast differentiation in vitro and exacerbated experimental fibrosis in vivo. PARP-1 deficiency induced a more severe fibrotic response to bleomycin with increased dermal thickening, hydroxyproline content and myofibroblast counts. Inhibition of PARylation also exacerbated fibrosis in Tsk-1 mice and in mice with topoisomerase-induced fibrosis. CONCLUSION: PARP-1 negatively regulates canonical TGFβ signalling in experimental skin fibrosis. The downregulation of PARP-1 in SSc fibroblasts may thus directly contribute to hyperactive TGFβ signalling and to persistent fibroblast activation in SSc.
EVALuna2:34150